FEMINISM IN ENGLISH LITERATURE OF THE 19TH AND 20TH CENTURIES - 528, Ms.Amolak1, Dr. Amit Dhawan2 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
As the centuries, the style of writing changed, and the need to talk about new things like sexuality, homosexuality, and the value of liberty became more clear. During the nineteenth century, writers began to talk about how important it was for women to be free and to be recognised. Because, for example, when women were finally able to vote and become more respected in society, writers wrote more openly about new issues. This is also one of the big changes in the evolution of literature. Some of the topics in twentieth-century literature would have been considered taboo in the 1800s, like the rejection of religion, homosexuality, and sexuality in general, as well as the rejection of religion.